2022
DOI: 10.1111/cas.15664
|View full text |Cite
|
Sign up to set email alerts
|

Cells with stem‐like properties are associated with the development of HPV18‐positive cervical cancer

Abstract: The cellular origins of cervical cancer and the histological differentiation of human papillomavirus (HPV)-infected cells remain unexplained. To gain new insights into the carcinogenesis and histological differentiation of HPV-associated cervical cancer, we focused on cervical cancer with mixed histological types. We conducted genomic and transcriptomic analyses of cervical cancers with mixed histological types. The commonality of the cellular origins of these cancers was inferred using phylogenetic analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…In addition, NPM3 showed higher expression in ADC than in SCC, which suggests that NPM3 can contribute to ADC development, which is a characteristic histopathological type for HPV18. Carcinogenesis of HPV18‐related cervical cancer is reportedly associated with stem cell‐like cells with multipotency 14‐16 . Our results support the stem cell carcinogenesis of HPV18‐related cancer; SCJ cells with HPV18 LCR activities were less differentiated than the other cells, and knockdown of NPM3 in HPV18‐infected cells decreased the expression of stem cell‐related genes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition, NPM3 showed higher expression in ADC than in SCC, which suggests that NPM3 can contribute to ADC development, which is a characteristic histopathological type for HPV18. Carcinogenesis of HPV18‐related cervical cancer is reportedly associated with stem cell‐like cells with multipotency 14‐16 . Our results support the stem cell carcinogenesis of HPV18‐related cancer; SCJ cells with HPV18 LCR activities were less differentiated than the other cells, and knockdown of NPM3 in HPV18‐infected cells decreased the expression of stem cell‐related genes.…”
Section: Discussionsupporting
confidence: 78%
“…Carcinogenesis of HPV18-related cervical cancer is reportedly associated with stem cell-like cells with multipotency. [14][15][16] Our results support the stem cell carcinogenesis of HPV18-related cancer; SCJ cells with HPV18 LCR activities were less differentiated than the other cells, and knockdown of NPM3 in HPV18-infected cells decreased the expression of stem cell-related genes. Although the precise mechanism by which NPM3 interacts with the HPV18 genome is still unknown, NPM3 acts as a histone chaperone that regulates chromatin structure and is involved in DNA replication, transcriptional regulation, and cell growth.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…One of the reasons for this is related to the histological characteristics of HPV18, which is more common in adenocarcinomas and small cell carcinomas among cervical cancers, and it is more difficult to detect precancerous lesions in these histological types than in squamous cell carcinomas [ 38 , 39 ]. However, the low detection rate of HPV18 in precancerous lesions cannot be explained by histological characteristics alone, and some unique mechanisms are thought to be involved in HPV18 carcinogenesis [ 37 , 40 ]. A study analyzing the cellular origin of mixed carcinoma of the uterine cervix reported that maintenance of stem cell-like components is important for HPV18 carcinogenesis [ 40 ].…”
Section: Natural History Of Hpv-related Cervical Lesions According To...mentioning
confidence: 99%
“…However, the low detection rate of HPV18 in precancerous lesions cannot be explained by histological characteristics alone, and some unique mechanisms are thought to be involved in HPV18 carcinogenesis [ 37 , 40 ]. A study analyzing the cellular origin of mixed carcinoma of the uterine cervix reported that maintenance of stem cell-like components is important for HPV18 carcinogenesis [ 40 ]. Although further studies are needed to elucidate HPV18-associated carcinogenesis, the low detection rate of precancerous lesions and the high incidence of invasive cancer suggest that HPV18-positive patients require more careful management than patients with other types of infection.…”
Section: Natural History Of Hpv-related Cervical Lesions According To...mentioning
confidence: 99%